PERANCANGAN SISTEM LAPORAN KEUANGAN DAN PERPAJAKAN BERBASIS EXCEL DALAM PENGENDALIAN PRIVE WARUNG SEMBAKO ARMIA - Armiani Sri Wahyuni (LP2M Politeknik Jambi, 2026)
MSMEs have a strategic role in the national economy, but still often face financial management constraints, especially in transaction recording, private takeover control, and Final Income Tax calculation. This problem causes a mixture of personal funds and business funds (commingling of funds) which has an impact on the inaccuracy of net profit and the erosion of business capital. This research was conducted on Armia Grocery Stores which experienced a decrease in profits due to unrecorded and uncontrolled private management. This research aims to design a simple financial and tax reporting system based on Microsoft Excel in accordance with SAK EMKM. The method used is qualitative descriptive with a case study approach through observation, interviews, and documentation. The results of the study show that the Excel-based system is able to improve the order of financial records, control prive, and produce a more accurate calculation of 0.5% Final Income Tax in accordance with Government Regulation No. 55 of 2022 so as to support sustainable business decision-making.